2019
DOI: 10.1063/1.5120120
|View full text |Cite
|
Sign up to set email alerts
|

Spin measurements of NV centers coupled to a photonic crystal cavity

Abstract: Nitrogen-vacancy (NV) centers feature outstanding properties like a spin coherence time of up to one second as well as a level structure offering the possibility to initialize, coherently manipulate and optically read-out the spin degree of freedom of the ground state. However, only about three percent of their photon emission are channeled into the zero phonon line (ZPL), limiting both the rate of indistinguishable single photons and the signal-to-noise ratio (SNR) of coherent spin-photon interfaces. We here … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 89 publications
(125 reference statements)
0
21
0
Order By: Relevance
“…First, single ions can be trapped easily for weeks and, thus, offer a much longer storage than that of single neutral atoms. [131] Second, the state of trapped ions can be detected near-deterministically by optical 171 Yb + . The transition 2 S 1∕2 to 2 P 1∕2 is pumped by a light with the wavelength of 369.5 nm.…”
Section: Quantum Network With Trapped Ionsmentioning
confidence: 99%
See 3 more Smart Citations
“…First, single ions can be trapped easily for weeks and, thus, offer a much longer storage than that of single neutral atoms. [131] Second, the state of trapped ions can be detected near-deterministically by optical 171 Yb + . The transition 2 S 1∕2 to 2 P 1∕2 is pumped by a light with the wavelength of 369.5 nm.…”
Section: Quantum Network With Trapped Ionsmentioning
confidence: 99%
“…[142] After the preparation of single ion-single photon entanglement, the photon can be used as a quantum bus to connect different nodes containing ions. In this spirit, in 2007, Moehring et al demonstrated the entanglement generation between two separated 171 Yb + . [143] In their experiment, two ions were trapped in two vacuum chambers separated by 1 m. The experimental apparatus is displayed in Figure 8.…”
Section: Quantum Network With Trapped Ionsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is challenging to inhibit the phonon relaxation process and improve the photon emission efficiency via the ZPL. One approach is to couple the NV centers to cavities so as to enhance the ZPL via the Purcell effect [167,168].…”
Section: Quantum Network With Nitrogen-vacancy Center In Diamondsmentioning
confidence: 99%